2014
DOI: 10.1038/leu.2014.296
|View full text |Cite
|
Sign up to set email alerts
|

A regimen combining the Wee1 inhibitor AZD1775 with HDAC inhibitors targets human acute myeloid leukemia cells harboring various genetic mutations

Abstract: AZD1775 targets the cell cycle checkpoint kinase Wee1 and potentiates genotoxic agent cytotoxicity through p53-dependent or -independent mechanisms. Here, we report that AZD1775 interacted synergistically with histone deacetylase inhibitors (HDACIs e.g., Vorinostat), which interrupt the DNA damage response (DDR), to kill p53-wild type or -deficient as well as FLT3-ITD leukemia cells in association with pronounced Wee1 inhibition and diminished cdc2/Cdk1 Y15 phosphorylation. Similarly, Wee1 shRNA knock-down sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
58
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(68 citation statements)
references
References 61 publications
9
58
1
Order By: Relevance
“…While we were performing our studies, Zhou et al published their study investigating the combination of Vorinostat, a pan-HDACI, with MK-1775 in AML. 45 In their study, the authors found diminished p-CDK1 following Vorinostat or MK-1775 treatment and further decrease after combined drug treatment, 45 which are similar to our results with panobinostat and MK-1775 treatment (Fig. 5).…”
Section: Discussionsupporting
confidence: 81%
“…While we were performing our studies, Zhou et al published their study investigating the combination of Vorinostat, a pan-HDACI, with MK-1775 in AML. 45 In their study, the authors found diminished p-CDK1 following Vorinostat or MK-1775 treatment and further decrease after combined drug treatment, 45 which are similar to our results with panobinostat and MK-1775 treatment (Fig. 5).…”
Section: Discussionsupporting
confidence: 81%
“…MLN4924 and belinostat interact synergistically in AML cell lines with various genetic backgrounds, whereas FLT3-ITD or p53 knockdown increase sensitivity MLN4924 interactions with belinostat in leukemia cell lines expressing wt or mutant p53 and/or FLT3-ITD, adverse prognostic markers in AML, 6 were first examined. Although sensitivity to MLN4924 alone varied between lines, MLN4924/belinostat coexposure significantly increased apoptosis in all AML lines (Figure 1A-B; supplemental Figure 1A), whereas p53-deficient cells (eg, U937; Figure 1B left panel) were more sensitive than wt p53 cells (eg, OCI-AML-3; Figure 1A left panel).…”
Section: Resultsmentioning
confidence: 99%
“…Primary AML (blasts .70% and viability .95%) or MDS samples and normal human cord blood (CB) CD34 1 cells were isolated as before. 6 Clinical, molecular, and cytogenetic characteristics of 6 selected patients are described in supplemental Table 1 (available on the Blood Web site).…”
Section: Cells and Reagentsmentioning
confidence: 99%
See 2 more Smart Citations